O novo ensino médio no Espírito Santo: o componente curricular projeto de vida na formação dos jovens - Silva, Asenate Rodrigues e (2023)
This dissertation proposes to investigate the curriculum changes approved by Law No. 13,415/2017 (BRAZIL, 2017), which establishes the Policy for the Promotion of the Implementation of Full-Time High Schools. The dissertation focuses on the curricular component "Life Project" in the New High School in Espírito Santo. We pose the research problem: What are the perceptions of high school students in ES about the curricular component "Life Project"? Therefore, the hypothesis that guides this work is that the curricular changes determined by the High School Reform implemented by Law No. 13,415/2017, lead to a depletion of the curriculum. The right to the development of knowledge, intellectual autonomy, and critical thinking does not have centrality in the formation of the subject. From this provisional assertion, our assumption is that the curricular component "Life Project," the axis of the New High School, proposes an education that emphasizes the individualistic socioemotional aspects in the formation of young people, aiming at disciplining subjectivities according to current market demands in the digital age. According to the curricular and operational guidelines for the Life Project, created in 2020, the component is the path traced between "who he is" and "who he wants to be", starting from the appropriation of the history of his personal life to project trajectories about his own desires for action in the environment where he lives and in the world” (SEDU, 2020). This study adopts a qualitative and exploratory nature perspective (GIL, 2002). As a theoretical and epistemological foundation, the research is guided by the Sociology of Public Action - Muller (2000), Muller and Surel (2002), Muller (2002), and Mény and Thoennig (2000) - in order to understand the complexities involved in the elaboration, implementation, and translation of public policy. In addition, this study is theoretically inspired by the works of Luc Boltanski and Ève Chiapello (2009) and Dardot, P. and Laval, C. (2017), authors who critically analyze the capitalist system today. The following methodological procedures were adopted: documentary analysis and questionnaire with students. The results showed that students have different perceptions about the curricular component called Life Project. The majority of them expressed a feeling of disinterest in the discipline or that it is insignificant for their school education. This leads us to presume that the humanist ideal of the emancipatory school has transmuted into an ideal of education service.